Socio-Spatial Determinants of Household Solid Waste Generation and Disposal Behaviour in Medium-Sized Cities in Osun State, Nigeria - Adenrele, Adeniyi Sunday (Geosfera Indonesia, 2026)
Rapid urbanisation and changing consumption patterns have intensified solid waste generation and unsustainable disposal practices in Nigerian cities. Although municipal solid waste management has been widely studied in metropolitan areas, limited evidence exists on the socio-spatial determinants of waste generation and disposal behaviour in medium-sized cities. This study examined these determinants in Osogbo, Ede, and Iwo, three medium-sized cities in Osun State. Primary data were collected from 244 household heads using multistage sampling across high- and low-density neighbourhoods. Descriptive statistics, multiple linear regression, multinomial logistic regression, and analysis of variance (ANOVA) were used to analyse waste generation, disposal behaviour, and willingness to pay for improved waste services. Results showed that household waste generation was significantly higher in high-density neighbourhoods than in low-density areas. Biodegradable materials, particularly food and vegetable waste, constituted the largest proportion of household waste (54.6–62.1%), while plastics dominated the non-biodegradable fraction. Regression identified household income, household size, and residential location as significant determinants of waste generation. Multinomial logistic regression indicated that higher household income and educational attainment reduced the likelihood of environmentally unsustainable disposal practices, whereas larger household size, high residential density, and greater distance to formal disposal facilities increased the likelihood of open burning and roadside dumping. Each additional kilometre to the nearest formal disposal facility increased the odds of roadside dumping or burial by approximately 85.5% (OR = 1.855). ANOVA revealed significant differences in willingness to pay according to household income, educational attainment, and proximity to formal disposal facilities (p < 0.05). The findings demonstrate that household waste management behaviour is a socio-spatial process shaped by interactions between socioeconomic conditions and spatial accessibility to waste management infrastructure. The study contributes by integrating waste generation, disposal behaviour, and willingness to pay within one analytical framework, providing policy-relevant evidence for context-specific and sustainable waste management strategies in urbanising cities.